2006
DOI: 10.1016/j.abb.2006.07.002
|View full text |Cite
|
Sign up to set email alerts
|

α-Tocopherol induces calnexin in renal tubular cells: Another protective mechanism against free radical-induced cellular damage

Abstract: Pre-administration of alpha-tocopherol is protective against oxidative renal tubular damage and subsequent carcinogenesis by ferric nitrilotriacetate (Fe-NTA) in rats. We searched for mechanisms other than the scavenging effect of alpha-tocopherol with microarray analyses, which implicated calnexin, a chaperone for glycoproteins. Renal mRNA levels of calnexin significantly increased 3h after an injection of Fe-NTA in rats fed a standard diet whereas those fed an alpha-tocopherol-supplemented diet showed an inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Total RNA was isolated with Isogen (Nippon Gene Co. Ltd., Tokyo, Japan), and the degree of gene expression was then evaluated with GeneChip analysis (Focus array; Affymetrix) as previously described. 23 Network analysis was performed using Ingenuity Pathways Analysis (Ingenuity Systems, Redwood City, CA).…”
Section: Gene Expression Microarraymentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was isolated with Isogen (Nippon Gene Co. Ltd., Tokyo, Japan), and the degree of gene expression was then evaluated with GeneChip analysis (Focus array; Affymetrix) as previously described. 23 Network analysis was performed using Ingenuity Pathways Analysis (Ingenuity Systems, Redwood City, CA).…”
Section: Gene Expression Microarraymentioning
confidence: 99%
“…The glyceraldehyde 3-phosphate dehydrogenase gene was used as an internal control as previously described. 23 PCR reactions for each target and control genes were performed in triplicate. Primer sequences used were as follows: ptprz1 based on NM_013080: forward, 5Ј-cccagctggtggttatgattcc-3Ј, and reverse, 5Ј-cgtgactttgaagctctctcgcaa-3Ј (104-bp product); cyclinD1 based on NM_171992: forward, 5Ј-tgtgccatccatgcggaaa-3Ј, and reverse, 5Ј-gacaagaaacggtccaggtagt-3Ј (114-bp product); c-myc based on NM_012603: forward, 5Ј-tgtctatttggggacagtgttc-3Ј, and reverse, 5Ј-ctgttagcgaagctcacgtt-3Ј (149-bp product); c-jun based on NM_021835: forward, 5Ј-gtgaaatgacagctgagtgtctg-3Ј, and reverse, 5Ј-gtcaacagtctggacttgtgg-3Ј (141-bp product); fra-1 based on NM_012953: forward, 5Ј-ctgctaagtgcagaaaccga-3Ј, and reverse, 5Ј-caaggcgttccttctgctt-3Ј (129-bp product); and CD44 based on NM_012924: forward, 5Ј-tttggtggcacacagcttg-3Ј, and reverse, 5Ј-atggaatacacctgcgtaacgg-3Ј (104-bp product).…”
Section: Rt-pcrmentioning
confidence: 99%
“…There is a possibility that α‐tocopheryl phosphate is a more efficient biomolecule 125 . We recently observed that one of the anti‐oxidant mechanisms of vitamin E is via inducing chaperone proteins associated with glycoproteins 126 …”
Section: Redox Regulation and Signal Cascades Under Oxidative Stressmentioning
confidence: 99%
“…125 We recently observed that one of the antioxidant mechanisms of vitamin E is via inducing chaperone proteins associated with glycoproteins. 126…”
Section: Redox Regulation and Signal Cascades Under Oxidative Stressmentioning
confidence: 99%